2013
DOI: 10.1097/dcr.0b013e3182759029
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Infliximab Therapy Does Not Increase Morbidity and Mortality After Laparoscopic Resection for Inflammatory Bowel Disease

Abstract: Infliximab is not associated with increased rates of postoperative complications after laparoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 32 publications
3
55
0
2
Order By: Relevance
“…Although severity scoring systems for UC exist [26], these data are not coded within HES. A few studies have managed to investigate the association of anti-TNF with postoperative complications and adjust for disease severity [5,[27][28][29][30]. Some of these studies reported an increased risk of postoperative complications with anti-TNF therapy [5,6,29] while the others reported no such association [27,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although severity scoring systems for UC exist [26], these data are not coded within HES. A few studies have managed to investigate the association of anti-TNF with postoperative complications and adjust for disease severity [5,[27][28][29][30]. Some of these studies reported an increased risk of postoperative complications with anti-TNF therapy [5,6,29] while the others reported no such association [27,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found an AL rate of 6·8 per cent in the corticosteroid group compared with 3·3 per cent in patients not treated with corticosteroid, but the duration and dose of treatment were heterogeneous. Infliximab alone may not alter AL risk, but in combination with other immune modulators can slow healing. There is evidence to suggest that mycophenolate mofetil, ciclosporin A, tacrolimus and everolimus all increase the risk of AL.…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…After full‐text review, we excluded 17 systematic reviews, three review articles, 14 non‐peer‐reviewed articles, three letters to the editor, two case series, nine articles with mixed data that could not be separated, one that included exposure to anti‐TNF agents after surgery, and one that enrolled patients with minor surgery. Finally, 20 eligible studies, including 19 cohort studies and one case‐control study, were subjected to qualitative review.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies reporting OR after multivariate analysis of post‐operative total complications, including disease severity, co‐morbidities, concomitant medications, and others (details are summarised in Table S1), were pooled with a summary effect adjusted OR of 1.53 (95% CI, 1.11‐2.09; I 2 = 43.8%; P = 0.058), indicating a significantly higher rate of complications in patients treated with anti‐TNF agents than in controls (Figure ). Seven studies reporting post‐operative infectious complications were pooled, and the adjusted OR was 2.09 (95% CI, 1.19‐3.65; I 2 = 62.1%; P = 0.015), indicating a significantly higher rate of complications in patients treated with anti‐TNF agents than in controls (Figure ). Three studies reporting post‐operative non‐infectious complications were pooled, and the adjusted OR was 1.18 (95% CI, 0.69‐2.01; I 2 = 0.0%; P = 0.933), indicating a nonsignificant association (Figure ).…”
Section: Resultsmentioning
confidence: 99%